Kif2 localizes to a subdomain of cortical endoplasmic reticulum that drives asymmetric spindle position - Vlad Costache (Nature Portfolio, 2017)
Early ascidian embryos have a cortical subdomain of endoplasmic reticulum (ER) that controls asymmetric spindle positioning driving unequal cell division. Here the authors show that the microtubule depolymerase Kif2 is localized to a cortical subdomain of the ER that is involved in asymmetric spindle positioning.